Evaluation of modified advanced locking plate system and polyaxial locking plate system with plate-rod and plating techniques for femur fracture repair in Dogs - G L, SWAROOP; DILIPKUMAR, D; PATIL, MANJUNATH (The Indian Journal of Animal Sciences, 2025)
The present study was conducted in twenty-four clinical cases of femoral fracture in dogs were divided into four Groups. The femoral fractures in dogs of Group I were repaired using mALPS plating, Group II were repaired by PAX plating, Group III were repaired using mALPS plate-rod construct and Group IV were repaired with PAX plate-rod construct. Based on clinical, physiological and radiological analysis, healing of the fractures was studied at intervals of 0, 15th, 30th, 60th and 90th post-operative days. Dog’s performance in fracture healing techniques with PAX plating, PRC – PAX, PRC – mALPS and mALPS plating Groups showed better weight-bearing on the fractured limb, immediately after the surgical repair while standing. Lameness grading in all the Groups showed that PAX had a statistically superior healing time in both PRC and plating techniques when compared with mALPS. Physiological parameters were fluctuated within normal physiological limits in all the Groups of animals suggesting that fracture healing period did not produced any changes in physiological parameters. Radiographic evaluation revealed that, fracture healing was slightly better in PAX plate when compared to mALPS and the comparison between the mALPS - PRC and the PAX - PRC revealed that PAX – PRC had slightly more rigid fixation when compared to mALPS – PRC.